The senses in late medieval England - Woolgar, Christopher Michael (Yale Univ. Press, 2006)
Ideas about the senses -- Touch, virtues, and holiness -- Sound and hearing -- The senses of the mouth: speech -- The senses of the mouth: taste -- Smell -- Vision -- Sensory environments and Episcopal households of the thirteenth and early fourteenth centuries -- Households of the late medieval queens of England -- The great household at the end of the Middle Ages -- Changing perceptions